Strategies for Enhancing Teacher Professionalism Through Academic Supervision in Islamic Educational Institutions - Rusmini Rusmini; Aprizal Aprizal; Refnil Yetti (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2026)
This article employs a Systematic Literature Review (SLR) with a conceptual explanatory orientation to synthesize and interpret findings from recent empirical and conceptual studies indexed in Scopus (Q1–Q4) and SINTA (S1–S4). Using thematic synthesis, the review analyzes patterns of supervisory practices, processes of pedagogical change, and contextual conditions that shape the effectiveness of academic supervision. The findings indicate that academic supervision functions effectively not as a procedural managerial activity, but as a relational and reflective pedagogical mechanism. Professional transformation occurs when supervisory feedback is internalized through reflective engagement, supported by trust based leadership relationships and aligned with institutional values. Conversely, supervision tends to produce administrative compliance rather than pedagogical change when implemented in a technocratic manner, irrespective of teachers’ professional meaning making processes. The review also reveals a recurring paradox in which systematic supervision and adequate teacher qualifications do not necessarily lead to sustainable professional growth. This article contributes to the supervision literature by shifting the analytical focus from outcomes to mechanisms, offering a conceptual explanation of both the effectiveness and failure of supervision within Islamic educational contexts. These findings extend existing theories of academic supervision by highlighting the mediating role of institutional values and relational dynamics in shaping teacher professionalism.Keywords: Academic Supervision; Teacher Professionalism; Islamic Educational Institutions.